Diagnostic challenges in complicated case of glioblastoma - Aghova, Tatiana; Lhotska, Halka; Lizcova, Libuse; Svobodova, Karla; Hodanova, Lucie; Janeckova, Karolina; Vucinic, Kim; Gregor, Martin; Konecna, Dora; Kramar, Filip; Soukup, Jiri; Netuka, David; et al. (Pathology oncology research, 2024)
Glioblastoma is the commonest primary malignant brain tumor, with a very poor prognosis and short overall survival. It is characterized by its high intra- and intertumoral heterogeneity, in terms of both the level of single-nucleotide variants, copy number alterations, and aneuploidy. Therefore, routine diagnosis can be challenging in some cases. We present a complicated case of glioblastoma, which was characterized with five cytogenomic methods: interphase fluorescence in situ hybridization, multiplex ligation-dependent probe amplification, comparative genomic hybridization array and single-nucleotide polymorphism, targeted gene panel, and whole-genome sequencing. These cytogenomic methods revealed classical findings associated with glioblastoma, such as a lack of IDH and TERT mutations, gain of chromosome 7, and loss of chromosome 10. At least three pathological clones were identified, including one with whole-genome duplication, and one with loss of 1p and suspected loss of 19q. Deletion and mutation of the TP53 gene were detected with numerous breakends on 17p and 20q. Based on these findings, we recommend a combined approach to the diagnosis of glioblastoma involving the detection of copy number alterations, mutations, and aneuploidy. The choice of the best combination of methods is based on cost, time required, staff expertise, and laboratory equipment. This integrated strategy could contribute directly to tangible improvements in the diagnosis, prognosis, and prediction of the therapeutic responses of patients with brain tumors.
Keywords: mutace; DNA Copy Number Variations; srovnávací genomová hybridizace; MLPA; aCGH/SNP; cytogenomics; jednonukleotidový polymorfismus; variabilita počtu kopií segmentů DNA; nádory mozku; lidé; Polymorphism, Single Nucleotide; gene panel; Mutation; glioblastom; prognóza; Glioblastoma; Male; nádorové biomarkery; diagnostics; Brain Neoplasms; Prognosis; Comparative Genomic Hybridization; Biomarkers, Tumor; hybridizace in situ fluorescenční; lidé středního věku; WGS; mužské pohlaví; In Situ Hybridization, Fluorescence; Middle Aged; I-FISH; Humans